A circular economy business model innovation process for the electrical and electronic equipment sector. (10th July 2021) - Pollard, Jennifer; Osmani, Mohamed; Cole, Christine; Grubnic, Suzana; Colwill, James
Abstract: Faced with a scarcity of materials, increasing quantities of waste, and low rate of recovery, the electrical and electronic equipment sector has become a key focus in the drive for a transition to the circular economy. An increasing body of work has addressed the integration of the circular economy at a business model level but there is a limited understanding of a sector-wide approach to circular economy business model innovation. Additionally, no studies have been identified that endeavoured to develop a circular economy business model innovation process for electrical and electronic manufacturers. To address this gap, this research adopted a qualitative approach via seven iterative workshops with key stakeholders in the electrical and electronic equipment sector to inform the development and refinement of a Circular Economy Business Model Innovation Process Framework. The resulting Framework, which has five-fold interconnected layers, provides electrical and electronic equipment manufacturers with a comprehensive layered process for developing and implementing a circular economy business model tailored to their business offerings. Using the manufacturer's business strategy as a starting point, the developed Framework prompts the integration of the circular economy into business practices. Influencing factors affecting the circular economy business model innovation process are addressed by identifying the associated challenges and opportunities and related policy. Finally, the Framework proposes circularity indicators relevant to electrical and electronic equipment, helping to ensure that the proposed circular economy actions are measurable and informed. Highlights: Exploration of circular economy business model innovation processes. Co-creation of a Circular Economy Business Model Innovation Process Framework with sector stakeholders. Identification of challenges, opportunities and policy influencing the innovation process. Development of circularity indicators proposed for the electrical and electronics equipment sector. Guidance for electrical and electronics equipment manufacturers using the Framework.